Prevalence and Genotype Distribution of HPV in Gynecological Patients: A Cross-Sectional Study - Noori, Raja A.; Salih, Azhar; Alhar, Hind AbdNoor Khudayer; Al Fatlawi, Sabah N. Mohammed; Al-Janabi, Asad A.; Hameed, Raghdah Maytham (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Human papillomavirus (HPV) is a prevalent sexually transmitted virus that can lead to genital warts or cancer. Over 100 HPV strains have been discovered, some classified as high-risk and others as low-risk. This study aimed to analyze the prevalence of HPV genotypes in patients with gynecological problems and to compare the frequency of low-risk and high-risk HPV infections. A cross-sectional study was performed. Five hundred patients were recruited who attended a gynecological clinic due to various reasons such as genital warts, itching, bleeding, or even asymptomatic cases discovered during routine visits in the period extending from January 2nd, 2017 to December 31st, 2022. Genotyping was performed using the Hybrispot technique, targeting 27 different HPV genotypes. DNA flow technology, a rapid and sensitive method, was utilized for the analysis. Out of the 500 patients, 109 tested positive for HPV, indicating 21.8% incidence among those seeking gynecological care. Among the HPV-positive patients, 59% had low-risk HPV, and 41% had high-risk HPV. The most common low-risk genotypes were HPV6 and HPV11, while the most common high-risk genotypes were HPV53, HPV58, HPV18, and HPV16. Several infrequent HPV genotypes were missed by the multiplex real-time PCR method. The study revealed a higher frequency of low-risk HPV compared to high-risk HPV, with no significant difference between the two groups.